Asymmetric nexus between stock price and exchange rate: Empirical evidence through NARDL - Rabia Luqman; Kasim Mansur; Mariashams Khakwani; Shanza Tabasum; Saadia Irshad (Ashwin Anokha Publications and Distributions, 2021)
Symmetric relationship between currency and equity markets has gained much attention among academicians and policy makers in the recent era. Many studies conducted on this relationship have concluded that there is short-run relationship between these variables and foundless evidence about a long-run relationship. Moreover, all previous studies supposed the linear or symmetrical relationship between these variables. This study aims to investigate that either stock price affects the exchange rate and exchange rate affect the stock price. Daily data of stock indices and real exchange rate for 14 countries includes Canada, France, Germany, Italy, Japan, UK, USA, Russia, Brazil, China, India, Mexico and South Africa and Pakistan has been considered as sample data for this study. Unit root test (ADF &PP), Johansen’s Cointegration test, Error Correction Model and Granger Causality is applied to test the short and long run relationship between the variable of study. To check the symmetrical and asymmetrical relationship between currency and equity markets, linear and non-linear autoregressive distributed lag (ARDL) are applied. Results have shown that there are asymmetrical linkages between the currencyand equity markets.